Structure-property correlations of synthetic eumelanin towards bioelectronic applications - Paulin, João Vitor [UNESP] (2021)
The natural pigment known as melanin has become a very promising material for many technological applications, but especially in the emerging area of organic bioelectronics due to its charge transport properties and biocompatibility. Thus, this thesis aimed to shed light on the optoelectronic properties of a series of melanin derivatives and apply such materials in organic devices. With this in mind, synthetic melanin derivatives were investigated using structural, optical, magnetic resonance and electrical techniques to elucidate the basic behavior of the materials as well as their charge transport properties. These set of characterizations included depth-profile X-ray photoelectron spectroscopy, photoluminescence, UV-Vis-NIR and ellipsometry spectroscopy, electron paramagnetic resonance, DC conductivity and electrochemical impedance spectroscopy under hydration control and neutron scattering. It was possible to show that soluble melanin synthesized in water behaves similarly to standard (and insoluble) melanin with slight variations that could be related small changes in the oxidation state of the samples or to different film thickness. On the other hand, the sulfonated melanin behaves like the standard one, indicating that these materials can be considered part of the “melanin family” of compounds. However, there were at least two key differences; it appears to have a lower ionic conductivity, most likely due to sulfonated groups replacing available conductive protons. However, this is compensated by the fact that sulfonated melanins exhibit easier thin-film formation on different surfaces, making it more attractive for device applications. We further demonstrated that SMel (one of the sulfonated melanin derivatives) is sensitive to pH in a carbon/graphene screen-printed electrode, that is, a sensor. This device can be considered a proof of concept that sulfonated melanin can act as transduction material for bioelectronics applications.